The Role and Transformation of Nora Performing Art as Recognized by UNESCO as an Intangible Cultural Heritage - Waiyawek, Pennapa (Connexion: Journal of Humanities and Social Sciences, 2023)
Nora is a valuable indigenous cultural heritage associated with the way of life of southern people for many generations. It represents a perfect combination between “science” and “arts”. Nora embeds a science of performing arts related to faith, religious rituals, superstition, spirits, deities and deceased ancestors. On the Nora is art in it aesthetic, delicate and strong moves to the rhythm of the unique music. There are exquisitely beautiful costumes and the style of the show is unique and unique. This enables Nora to live in a society that is dynamic or a society that is constantly changing. Nora has been declared Intangible Heritage of wisdom by the United Nations Educational, Scientific and Cultural Organization (UNESCO) in 2021 under the name “Nora, Dance Drama in Southern Thailand”. The article on the role and transformation of Nora performing art as recognized by UNESCO as an intangible cultural heritage is an academic article that aims to analyze the role and transformation of Nora performing art as recognized by UNESCO as an intangible cultural heritage. It consists of the following topics: (1) The role and background of Nora performance that appears in literature, (2) Nora performance as an intangible cultural heritage, (3) Nora performance as an art of cultural heritage, (4) The role of Nora performance in today’s society, (5) The evolution of Nora’s performance over time, (6) Factors or conditions that cause Nora performance to be recognized as a world intangible cultural heritage. The analysis results found that in an era where the world is facing rapid change, Nora still prevails an important southern Thai culture rooted in the local area of the south. It is one of the cultures of mankind and progressing in parallel with the changes. However, Nora still plays the same role in creating entertainment, beliefs, rituals, reflecting the progress of society. Including the transfer of knowledge, ideas, beliefs, faith from one generation to the next.